The influence of entrepreneurial orientation, competitive strategy and organizational culture on the performance of private universities in Dhaka, Bangladesh - Rahim, Md Abdur (Tanjong Malim, 2021)
The influence of entrepreneurial orientation, competitive strategy and organizational culture on the performance of private universities in Dhaka, Bangladesh by Rahim, Md Abdur